Diffuse Laminar Endocervical Glandular Hyperplasia: A Case Report. Issue 6 (1st July 2009) - Dainty, Louis A.; Krivak, Thomas C.; Webb, Joel C.; Zahn, Christopher M.; Elkas, John C.; Chernofsky, Mildred R.; Rose, G. Scott; Maxwell, G. Larry
Abstract : Background: Diffuse laminar endocervical glandular hyperplasia is extremely rare with only 14 cases reported in the literature. Diffuse laminar endocervical glandular hyperplasia is a benign lesion that is easily confused with malignancy. Case Report: We present a 22-year-old woman referred to our gynecologic oncology service with a 2.0 × 4.0-cm exophytic cervical mass. Colposcopic-directed cervical biopsies were diagnosed as adenocarcinoma, suggestive of minimal deviation adenocarcinoma. Computed tomographic scans of the abdomen and the pelvis failed to reveal any metastatic foci. A radical abdominal hysterectomy with pelvic and para-aortic lymph node sampling was performed without complications. Final pathology revealed diffuse laminar endocervical glandular hyperplasia. Conclusions: Diffuse laminar endocervical glandular hyperplasia is an uncommon histological type of pseudoneoplastic glandular lesions that may be found in the cervix, and this entity should be considered in the differential diagnosis of a potentially malignant endocervical glandular lesion.